Manajemen Penerapan Pendidikan Islam Berbasis Multikultural di SMA Negeri 2 Kota Tanjungbalai - Shopiana, Shopiana (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
Multicultural-based Islamic education management is a strategic approach aimed at promoting understanding, acceptance, and appreciation of diversity in educational settings. This concept is not only relevant to national life but also crucial for schools, particularly in shaping students' character to be tolerant and have a broad perspective. The purpose of this study is to describe how multicultural-based Islamic education management is implemented at SMA Negeri 2 Kota Tanjungbalai. The research method used is qualitative, with data collected through observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of multicultural-based Islamic education in this school is carried out through three main aspects: first, the integration of multicultural values into teaching materials and the curriculum; second, the implementation of school activities that encourage intercultural interaction, such as interfaith dialogue, religious events involving students from various backgrounds, and tolerance-based competitions; third, the use of participatory teaching methods that encourage open discussion about diversity. This adaptive management of Islamic education, which responds to social realities, further strengthens Islamic values such as tolerance, justice, and compassion in educational practice. In conclusion, multicultural-based Islamic education at SMA Negeri 2 Kota Tanjungbalai has been implemented systematically and has made a positive contribution to creating an inclusive and harmonious learning environment.ABSTRAKManajemen pendidikan Islam berbasis multikultural merupakan pendekatan strategis yang bertujuan untuk mempromosikan pemahaman, penerimaan, dan penghargaan terhadap keragaman dalam lingkungan pendidikan. Konsep ini tidak hanya relevan bagi kehidupan nasional tetapi juga krusial bagi sekolah, terutama dalam membentuk karakter siswa agar toleran dan memiliki perspektif yang luas. Tujuan penelitian ini adalah untuk menggambarkan bagaimana manajemen pendidikan Islam berbasis multikultural diterapkan di SMA Negeri 2 Kota Tanjungbalai. Metode penelitian yang digunakan adalah kualitatif, dengan data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi pendidikan Islam berbasis multikultural di sekolah ini dilakukan melalui tiga aspek utama: pertama, integrasi nilai-nilai multikultural ke dalam bahan ajar dan kurikulum; kedua, pelaksanaan kegiatan sekolah yang mendorong interaksi antarbudaya, seperti dialog antaragama, acara keagamaan yang melibatkan siswa dari berbagai latar belakang, dan kompetisi berbasis toleransi; ketiga, penggunaan metode pengajaran partisipatif yang mendorong diskusi terbuka tentang keragaman. Pengelolaan pendidikan Islam yang adaptif ini, yang merespons realitas sosial, semakin memperkuat nilai-nilai Islam seperti toleransi, keadilan, dan kasih sayang dalam praktik pendidikan. Kesimpulannya, pendidikan Islam berbasis multikultural di SMA Negeri 2 Kota Tanjungbalai telah diterapkan secara sistematis dan memberikan kontribusi positif dalam menciptakan lingkungan belajar yang inklusif dan harmonis.